DAMPAK PENGGUNAAN APLIKASI TIKTOK DI KAMPUNG DURI KECAMATAN SOREANG KELURAHAN BUKIT HARAPAN KOTA PAREPARE - Widya Citra Dewi; Haramain, Muhammad; Sulaiman, Nining Artianasari (Journal of Media and Communication Studies, 2025)
This study is motivated by the increasing use of the TikTok application among adolescents and its potential impact on narcissistic behavior and social life in Kampung Duri, Soreang Subdistrict, Bukit Harapan Village, Parepare City. The research aims to explore the intensity of TikTok usage, the dramaturgic portrayal of narcissistic behavior, and its impacts in the area. A descriptive qualitative approach was employed, utilizing observation and documentation as data collection techniques. The findings indicate that TikTok usage in Kampung Duri is notably high, particularly among adolescents who are creative, predominantly content consumers, and frequent users of filters. TikTok usage influences adolescent narcissism and yields positive impacts such as enhanced creativity, access to information, expanded social connections, therapeutic healing, and business opportunities, alongside negative impacts including time wastage, unrestricted age access, and hate speech. These findings underscore the importance of managing TikTok usage to maximize benefits and minimize adverse effects, particularly on adolescents’ psychosocial development